HeiCuBeDa Hilprecht - Heidelberg Cuneiform Benchmark Dataset for the Hilprecht Collection - Mara, Hubert (Universität, 2019)
The number of known cuneiform tablets is assumed to be in the hundreds of thousands. A fraction has been published by printing photographs and manu...